A novel COL4A5 splicing mutation causes alport syndrome in a Chinese family - Suyun Chen; Guangbiao Xu; Zhixin Zhao; Juping Du; Bo Shen; Chunping Li (BMC, 2024)
Abstract Background Alport syndrome (AS) is characterised by haematuria, proteinuria, a gradual decline in kidney function, hearing loss, and eye abnormalities. The disease is caused by mutations in COL4An (n = 3, 4, 5) that encodes 3-5 chains of type IV collagen in the glomerular basement membrane. AS has three genetic models: X-linked, autosomal recessive, and autosomal dominant. The most common type of AS is X-linked AS, which is caused by COL4A5. Methods We enrolled children with renal insufficiency and a family history of kidney disorders. The proband was identified using whole-exome sequencing. Sanger sequencing was performed to verify the mutation site. Minigene technology was used to analyse the influence of mutant genes on pre-mRNA shearing, and the Iterative Threading ASSEmbly Refinement (I-TASSER) server was used to analyse the protein structure changes. Results The proband, together with her mother and younger brother, displayed microscopic haematuria and proteinuria, Pathological examination revealed mesangial hyperplasia and sclerosis. A novel mutation (NM_000495.5 c.4298-8G > A) in the intron of the COL4A5 gene in the proband was discovered, which was also present in the proband's mother, brother, and grandmother. In vitro minigene expression experiments verified that the c.4298-8G > A mutation caused abnormal splicing, leading to the retention of six base pairs at the end of intron 46. The I-TASSER software predicted that the mutation affected the hydrogen-bonding structure of COL4A5 and the electrostatic potential on the surface of the protein molecules. Conclusions Based on the patient's clinical history and genetic traits, we conclude that the mutation at the splicing site c.4298-8G > A of the COL4A5 gene is highly probable to be the underlying cause within this particular family. This discovery expands the genetic spectrum and deepens our understanding of the molecular mechanisms underlying AS.